Emulsion type oil gas plugging material as well as preparation method and application thereof

Through the preparation of emulsion type oil and gas sealing materials, the combination of rubber grafted gas-sensitive materials and oil-in-water emulsions is used to solve the problems of poor compatibility of sealing materials and insensitive to short-chain gas hydrocarbons in the prior art, and the effective sealing and blocking of oil and gas channels in micro-cracks under oil and gas triggering conditions is achieved.

CN119505279APending Publication Date: 2025-02-25CHANGCHUN INSTITUTE OF APPLIED CHEMISTRY CHINESE ACADEMY OF SCIENCES
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202311057106.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-22
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

In the prior art, the sealing material has poor compatibility with the cement slurry system and does not have sensitive response characteristics to short-chain gaseous hydrocarbons, making it difficult to effectively seal the oil and gas channels in the micro-cracks.

Method used

Emulsion type oil and gas sealing material is used, and its preparation method includes the preparation of rubber grafted gas-sensitive material and the preparation of oil-in-water emulsion. Rubber grafted gas-sensitive materials are prepared by graft polymerization and mixed with solid particles such as modified SiO2 to form an O/W emulsion, which has good cement slurry system compatibility and response characteristics that are sensitive to short-chain gaseous hydrocarbons.

Benefits of technology

Under the triggering conditions of oil or gas, the emulsion type oil and gas sealing material can swell itself, block or block the oil and gas channels in the microcracks, and has excellent effects of good stability, wide particle size distribution, and good compatibility with the cement slurry system.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses an emulsion type oil gas plugging material and a preparation method and application thereof, and belongs to the technical field of functional materials. The invention provides a preparation method of an emulsion type oil and gas plugging material aiming at the problems that a plugging material in the prior art is poor in compatibility with a cement paste system and has no sensitive response characteristic to short-chain gaseous hydrocarbons. The method specifically comprises the following steps: preparing a rubber grafted gas-sensitive material from a monomer solution containing an acrylate monomer, an alkyl olefine acid monomer and a styrene monomer, rubber particles and a separant, dispersing the rubber grafted gas-sensitive material in toluene as an oil phase, mixing the oil phase with a water phase containing a surfactant, homogenizing, and emulsifying to form an O / W emulsion. The emulsion type oil and gas blocking and plugging material provided by the invention is relatively good in stability and relatively wide in particle size distribution, has good compatibility with a cement paste system, shows sensitive response characteristics to gaseous hydrocarbons, and can realize blocking and plugging of oil and gas channels in multi-scale microcracks under a gas triggering condition.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of functional materials, and specifically relates to an emulsion type oil and gas plugging material and its preparation method and application. Under the triggering condition of oil or gas, the emulsion type oil and gas plugging material can swell itself to block or plug the oil and gas channels in microcracks. Background Art

[0002] At present, there is a huge demand for the development of natural gas, shale gas and other gas wells in China, and the extremely high oil and gas pressure underground often causes cementing annulus pressure and workover pressure construction. A large number of oil and gas channels are easily formed in the cementing annulus and various working interfaces of recovery, as well as micro-cracks related to the interface. These oil and gas crossflow channels bring great damage and hidden dangers to the integrity of the completed wellbore and the recovery and post-processing work after completion. Therefore, it is of great significance to block and block the oil and gas crossflow and the oil and water blockage of the micro-crack oil and gas channels at the downhole interface.

[0003] At present, the oil and gas crossflow and oil-water blocking problems are mainly solved by using plugging agents or plugging materials. The plugging materials are generally divided into granular plugging agents and resin liquid plugging agents. Among them, granular plugging agents are mainly inorganic granular plugging agents such as cement and clay. After being injected into the cracks, these plugging agents undergo hydration reactions triggered by water and solidify, thereby achieving the purpose of blocking; however, granular plugging agents are mainly compounded with cement by dry mixing, which is more complicated to operate. Moreover, this type of plugging agent does not solidify when encountering oil and gas, that is, it is not sensitive to oil and gas, and it is difficult to achieve the blocking of oil and gas crossflow channels. After the resin liquid plugging agent is injected, it contacts the water layer and forms a solid resin with a certain strength under the action of the curing agent, thereby blocking the hole plug; however, although this type of plugging material has a certain effect on the overall oil and gas blocking construction in the wellbore, due to the poor compatibility of the liquid plugging agent with the cement slurry system, its plugging and blocking effect on oil and gas in various interfaces or small cracks in the system is not obvious. Therefore, there is an urgent need to develop a plugging material that has good compatibility with the cement slurry system and has sensitive response characteristics to short-chain gaseous hydrocarbons. Summary of the invention

[0004] In order to solve the problem that the plugging materials in the prior art have poor compatibility with the cement slurry system and have no sensitive response characteristics to short-chain gaseous hydrocarbons, the present invention provides an emulsion-type oil and gas blocking and plugging material and a preparation method thereof. The emulsion-type oil and gas blocking and plugging material provided by the present invention has good compatibility with the cement slurry system and has sensitive response characteristics to short-chain gaseous hydrocarbons (carbon number ≤ 4). Under the triggering conditions of oil or gas, it can swell itself to block or plug the oil and gas channels in microcracks.

[0005] In order to achieve the above technical effects, the present invention provides the following technical solutions:

[0006] The present invention provides a method for preparing an emulsion type oil and gas plugging material, the preparation method comprising the following steps:

[0007] (1) Preparation of rubber grafted gas-sensitive materials:

[0008] a) mixing one or a combination of any two or more of an acrylate monomer, an alkylene acid monomer and a styrene monomer with a solvent to obtain a monomer solution;

[0009] b) swelling the non-polar or weakly polar rubber particles in the monomer solution of step a) to obtain a prepolymer;

[0010] c) mixing the prepolymer described in b) with a release agent, carrying out a graft polymerization reaction under initiation polymerization conditions, and drying and crushing the product to obtain a rubber grafted gas-sensitive material;

[0011] (2) Preparation of oil-in-water emulsion:

[0012] A) dispersing the rubber grafted gas-sensitive material obtained in step (1) in toluene as an oil phase;

[0013] B) dispersing solid particles having a certain hydrophilicity (water contact angle between 15-80°), including modified SiO2, modified cellulose, modified starch, etc., as surfactants in water as the aqueous phase;

[0014] C) mixing the oil phase described in step A) and the water phase described in step B), and homogenizing and emulsifying to obtain an O / W emulsion.

[0015] In one embodiment of the present invention, the solvent in step a) is any one of benzene, toluene or xylene.

[0016] In one embodiment of the present invention, the total mass fraction of the monomers in step a) is 20%-40%.

[0017] In one embodiment of the present invention, the acrylate monomer in step a) can be hexadecyl methacrylate, octadecyl acrylate, or the like.

[0018] In one embodiment of the present invention, the alkyl olefinic acid monomer in step a) can be undecylenic acid or the like.

[0019] In one embodiment of the present invention, the rubber particles in step b) are ethylene propylene rubber particles with a median particle size of 5 mm or isoprene rubber particles with a median particle size of 5 mm, and the swelling time is 6 hours.

[0020] In one embodiment of the present invention, after the non-polar or weakly polar rubber particles are mixed with the monomer solution in step b), the mass fraction of the non-polar or weakly polar rubber particles is 30%.

[0021] In one embodiment of the present invention, the mass ratio of the prepolymer to the isolation agent in step c) is 1:1, and the polymerization is initiated by high-energy electron irradiation at room temperature with an irradiation intensity of 120 kGy.

[0022] In one embodiment of the present invention, the release agent in step c) is white carbon black.

[0023] In one embodiment of the present invention, the drying condition in step c) is vacuum drying at 50° C. for 12 hours.

[0024] In one embodiment of the present invention, the mass fraction of the rubber grafted gas-sensitive material in the oil phase in step A) is 50%.

[0025] In one embodiment of the present invention, the mass fraction of solid particles in the aqueous phase in step B) is 0.5%-4%.

[0026] In one embodiment of the present invention, the volume ratio of the oil phase to the water phase in step C) is (4:6)-(6:4).

[0027] In one embodiment of the present invention, the homogenization speed in step C) is 10 krpm-20 krpm, and the emulsification time is 2 min.

[0028] The present invention also provides an emulsion type oil and gas plugging material prepared by the above preparation method.

[0029] The present invention also provides the use of the emulsion type oil and gas plugging material prepared by the above preparation method in blocking or plugging oil and gas channels.

[0030] Beneficial effects of the present invention:

[0031] It can be seen from the above test results that the emulsion-type oil and gas blocking and plugging material provided by the present invention exhibits sensitive response characteristics to gaseous hydrocarbons, and can achieve the blocking and plugging of oil and gas channels in microcracks under gas-triggered conditions; at the same time, the obtained oil and gas blocking and plugging material has good stability, a wide particle size distribution, good compatibility with the cement slurry system, and exhibits excellent oil and gas plugging effects under the wide particle size distribution, and can effectively achieve the blocking and plugging of oil and gas channels in multi-scale microcracks under gas-triggered conditions. DETAILED DESCRIPTION

[0032] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with specific embodiments. The experimental methods used in the following examples are all conventional methods unless otherwise specified, and the materials, reagents, methods and instruments used are all conventional materials, reagents, methods and instruments in the art unless otherwise specified, and those skilled in the art can obtain them through commercial channels.

[0033] Embodiment 1:

[0034] Hexadecyl methacrylate, undecylenic acid and styrene are dissolved in xylene to prepare a monomer solution with a total monomer mass concentration of 30wt%, wherein the mass fraction of hexadecyl methacrylate is 20.0%, the mass fraction of undecylenic acid is 7.0%, the mass fraction of styrene is 3.0%, and the rest is xylene. Ethylene-propylene rubber particles with a median particle size of 5mm are subjected to diffusion-controlled swelling in the monomer solution for 6 hours to obtain a prepolymer, wherein the mass fraction of ethylene-propylene rubber particles is 30%. After adding 50wt% of white carbon black to the obtained prepolymer, high-energy electron irradiation is carried out at room temperature to induce the monomer to undergo graft polymerization reaction inside and on the surface of the rubber particles, and the irradiation intensity is 120kGy; then the product is vacuum dried at 50°C for 12 hours and crushed to obtain a rubber grafted gas-sensitive material. Weigh 0.1 g of modified starch (HBPS), dissolve it in 9.9 g of water as the aqueous phase, and use 10 g of toluene solution (containing 5 g of rubber-grafted gas-sensitive material) as the oil phase. Take 4 g of the aqueous phase and 6 g of the oil phase, mix the two, and emulsify them for 120 s at 15 krpm using an IKA Ultra Turrax T18 homogenizer to obtain an O / W emulsion.

[0035] Embodiment 2:

[0036] Hexadecyl methacrylate, undecylenic acid and styrene are dissolved in xylene to prepare a monomer solution with a total monomer mass concentration of 20wt%, wherein the mass fraction of hexadecyl methacrylate is 14.0%, the mass fraction of undecylenic acid is 4.0%, the mass fraction of styrene is 2.0%, and the rest is xylene. Ethylene-propylene rubber particles with a median particle size of 5mm are subjected to diffusion-controlled swelling in the monomer solution for 6 hours to obtain a prepolymer, wherein the mass fraction of ethylene-propylene rubber particles is 30%. After adding 50wt% of white carbon black to the obtained prepolymer, high-energy electron irradiation is carried out at room temperature to induce the monomer to undergo graft polymerization reaction inside and on the surface of the rubber particles, and the irradiation intensity is 120kGy; then the product is vacuum dried at 50°C for 12 hours and crushed to obtain a rubber grafted gas-sensitive material. Weigh 0.1 g of modified starch (HBPS), dissolve it in 9.9 g of water as the aqueous phase, and use 10 g of toluene solution (containing 5 g of rubber-grafted gas-sensitive material) as the oil phase. Take 4 g of the aqueous phase and 6 g of the oil phase, mix the two, and emulsify them for 120 s at 15 krpm using an IKA Ultra Turrax T18 homogenizer to obtain an O / W emulsion.

[0037] Embodiment 3:

[0038] Hexadecyl methacrylate, undecylenic acid and styrene are dissolved in xylene to prepare a monomer solution with a total monomer mass concentration of 40wt%, wherein the mass fraction of hexadecyl methacrylate is 28.0%, the mass fraction of undecylenic acid is 8.0%, the mass fraction of styrene is 4.0%, and the rest is xylene. Ethylene-propylene rubber particles with a median particle size of 5mm are subjected to diffusion-controlled swelling in the monomer solution for 6 hours to obtain a prepolymer, wherein the mass fraction of ethylene-propylene rubber particles is 30%. After adding 50wt% of white carbon black to the obtained prepolymer, high-energy electron irradiation is carried out at room temperature to induce the monomer to undergo graft polymerization reaction inside and on the surface of the rubber particles, and the irradiation intensity is 120kGy; then the product is vacuum dried at 50°C for 12 hours and crushed to obtain a rubber grafted gas-sensitive material. Weigh 0.1 g of modified starch (HBPS), dissolve it in 9.9 g of water as the aqueous phase, and use 10 g of toluene solution (containing 5 g of rubber-grafted gas-sensitive material) as the oil phase. Take 4 g of the aqueous phase and 6 g of the oil phase, mix the two, and emulsify them for 120 s at 15 krpm using an IKA Ultra Turrax T18 homogenizer to obtain an O / W emulsion.

[0039] Embodiment 4:

[0040] The difference from Example 1 is that in the preparation process of the water-in-water emulsion, the volume ratio of the water phase to the oil phase is different from that in Example 1, specifically as follows: 0.1 g HBPS is weighed, dissolved in 9.9 g water as the water phase, 10 g toluene solution (containing 5 g rubber-grafted gas-sensitive material) is used as the oil phase, 5 g of the water phase and 5 g of the oil phase are taken, the two are mixed and emulsified for 120 s at 15 krpm using an IKA Ultra Turrax T18 homogenizer to obtain an O / W emulsion.

[0041] Embodiment 5:

[0042] The difference from Example 1 is that in the preparation process of the water-in-water emulsion, the volume ratio of the water phase to the oil phase is different from that in Example 1, specifically as follows: 0.1 g HBPS is weighed, dissolved in 9.9 g water as the water phase, 10 g toluene solution (containing 5 g rubber-grafted gas-sensitive material) is used as the oil phase, 6 g of the water phase and 4 g of the oil phase are taken, the two are mixed and emulsified for 120 s using an IKA Ultra Turrax T18 homogenizer at 15 krpm to obtain an O / W emulsion.

[0043] Embodiment 6:

[0044] The difference from Example 1 is that in the preparation process of the oil-in-water emulsion, the mass fraction of solid particles in the water phase is different from that in Example 1, specifically as follows: 0.05 g HBPS is weighed and dissolved in 9.95 g water as the water phase.

[0045] Embodiment 7:

[0046] The difference from Example 1 is that in the preparation process of the oil-in-water emulsion, the mass fraction of solid particles in the water phase is different from that in Example 1, specifically as follows: 0.2 g HBPS is weighed and dissolved in 9.8 g water as the water phase.

[0047] Embodiment 8:

[0048] The difference from Example 1 is that in the preparation process of the oil-in-water emulsion, the mass fraction of solid particles in the water phase is different from that in Example 1, specifically as follows: 0.4 g HBPS is weighed and dissolved in 9.6 g water as the water phase.

[0049] Embodiment 9:

[0050] The difference from Example 1 is that in the preparation process of the oil-in-water emulsion, the homogenization speed is different from that of Example 1, specifically as follows: 4 g of the water phase and 6 g of the oil phase are taken, the two are mixed, and then emulsified for 120 s at 10 krpm using an IKA Ultra Turrax T18 homogenizer to obtain an O / W emulsion.

[0051] Embodiment 10:

[0052] The difference from Example 1 is that in the preparation process of the oil-in-water emulsion, the homogenization speed is different from that of Example 1, specifically as follows: 4 g of the water phase and 6 g of the oil phase are taken, the two are mixed, and then emulsified for 120 s at 20 krpm using an IKA Ultra Turrax T18 homogenizer to obtain an O / W emulsion.

[0053] Embodiment 11:

[0054] The difference from Example 1 is that in the preparation process of the rubber grafted gas-sensitive material, isoprene rubber particles with a median particle size of 5 mm are selected.

[0055] Example 12: The difference from Example 1 is that in the preparation process of the rubber grafted gas-sensitive material, octadecyl acrylate, methyl methacrylate and styrene are dissolved in xylene to prepare a monomer solution with a total monomer mass concentration of 30wt%, wherein the mass fraction of octadecyl acrylate is 20.0%, the mass fraction of methyl methacrylate is 7.0%, the mass fraction of styrene is 3.0%, and the rest is xylene.

[0056] Performance Test:

[0057] (1) Stability test: The multiple emulsions prepared in Examples 1-12 were centrifuged at 4000 r for 5 min. After centrifugation, the layer heights of the multiple emulsions prepared in Examples 1-12 were recorded. The results are shown in Table 1.

[0058] (2) Particle size test: The particle size of the emulsion droplets prepared in Examples 1-12 was tested by light scattering method. The results are shown in Table 1.

[0059] (3) Gas sensitivity test: 1.0 g (denoted as M0) of the emulsion prepared in Examples 1-3 above was placed in a sealed container, and natural gas was added into the container after sealing. After the container was kept pressurized for 72 hours, the pressure was released and the sample was taken out and weighed (denoted as Me). The swelling ratio of the sample in natural gas was Qq = (Me-M0) / M0×100%; the test results are shown in Table 2.

[0060] Table 1 Emulsion stability and emulsion droplet size test results obtained in Examples 1-12

[0061]

[0062] Table 2 Test results of swelling ratio of the emulsions prepared in Examples 1-3 in natural gas

[0063]

[0064] As shown in Table 1, the emulsions prepared in Examples 1-12 hardly stratify after centrifugation, indicating that they have good stability and can be placed at room temperature for at least one month. The droplet size data of the emulsions prepared in Examples 1-12 show that the droplet size of the emulsions can be simply adjusted by adjusting the emulsification speed, oil-water ratio, stabilizer dosage and other conditions, so as to be suitable for plugging multi-scale microcracks.

[0065] As can be seen from Table 2, the emulsions prepared in Examples 1-12 swell after contacting the gas, and the greater the swelling ratio, the better the sensitivity to the gas response.

[0066] It can be seen from the above test results that the emulsion-type oil and gas blocking and plugging material provided by the present invention exhibits sensitive response characteristics to gaseous hydrocarbons, and can achieve the blocking and plugging of oil and gas channels in microcracks under gas-triggered conditions; at the same time, the obtained oil and gas blocking and plugging material has good stability and a wide particle size distribution, and exhibits excellent oil and gas plugging effects under this wide particle size distribution, and can effectively achieve oil and gas blocking and plugging in microcracks.

[0067] Although the present invention has been disclosed as above in the form of preferred embodiments, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.

Claims

1. A method for preparing an emulsion type oil and gas plugging material, characterized in that: The preparation method comprises the following steps: (1) Preparation of rubber grafted gas-sensitive materials: a) mixing one or a combination of any two or more of an acrylate monomer, an alkylene acid monomer and a styrene monomer with a solvent to obtain a monomer solution; b) swelling the non-polar or weakly polar rubber particles in the monomer solution of step a) to obtain a prepolymer; c) mixing the prepolymer described in b) with a release agent, carrying out a graft polymerization reaction under initiation polymerization conditions, and drying and crushing the product to obtain a rubber grafted gas-sensitive material; (2) Preparation of oil-in-water emulsion: A) dispersing the rubber grafted gas-sensitive material obtained in step (1) in toluene as an oil phase; B) dispersing solid particles having a water contact angle between 15° and 80° in water as a surfactant as an aqueous phase; C) mixing the oil phase described in step A) and the water phase described in step B), and homogenizing and emulsifying to obtain an oil-in-water emulsion.

2. The preparation method according to claim 1, characterized in that: In step a), the solvent is any one of benzene, toluene or xylene, and the total mass fraction of the monomers is 20%-40%.

3. The preparation method according to claim 1, characterized in that: In step c), the mass ratio of the prepolymer to the isolation agent is 1:1, and the polymerization is initiated by high-energy electron irradiation at room temperature with an irradiation intensity of 120 kGy.

4. The preparation method according to claim 1, characterized in that: Step A) The mass fraction of the rubber grafted gas-sensitive material in the oil phase is 50%.

5. The preparation method according to claim 1, characterized in that: Step B) The solid particles are any one of modified SiO2, modified cellulose and modified starch.

6. The preparation method according to claim 1, characterized in that: Step B) The mass fraction of solid particles in the aqueous phase is 0.5%-4%.

7. The preparation method according to claim 1, characterized in that: In step C), the volume ratio of the oil phase to the water phase is (4:6)-(6:4).

8. The preparation method according to claim 1, characterized in that: Step C) The homogenizing speed is 10krpm-20krpm, and the emulsification time is 2min.

9. An emulsion type oil and gas plugging material prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the emulsion type oil and gas plugging material prepared by the preparation method according to any one of claims 1 to 8 in blocking or plugging oil and gas channels.

Citation Information

Patent Citations

  • Oil-gas blocking and sealing material

    CN108276723A

  • Preparation method of high-internal-phase emulsion with stable cellulose nano-crystals

    CN108530649A

  • Composite emulsion with high interfacial tension and high interfacial modulus as well as preparation method and application of composite emulsion

    CN115975617A

  • Porous polymers which have particles on the pores surface, preparing method thereof and usages thereof

    KR1020180043871A

  • An oil-in-water emulsion containing no surfactant and use thereof

    US20160175432A1